Counseling Psychology : An Integrated Positive Psychology Approach - Chao, Ruth Chu-Lien (Chichester, West Sussex Wiley Blackwell, 2015)
Counseling Psychology: An Integrated Positive Approach introduces a new dimension in counseling psychology which includes both symptom treatment and positive psychology; this unique approach guides readers to enhance clients positive potential, rather than focusing solely on the treatment of clients negative symptoms
Include Reference and Index
Keywords: Counseling psychology